Design Proposal for Riverbanks Settlement Resilience through Respect to Site Approach - Avinda T. A. Vielandy; FX. Teddy Badai Samodra (IPTEK Journal of Proceedings Series, 2018)
In urban environment, the growing number of population increases the high level of housing needs, while publicly provided housing is sufficient. This is the main cause of the emergence of slums. This design research aims to upgrade the riverbank slum into a green settlement with improved housing quality by implementing six principles of Green Architecture into design. Field measurement and interview were conducted to obtain data for simulation using Ecotect Analysis and ANSYS Fluent software. The result highlighted that resilience design conducted through respect to site as on of the green architecture principles has the capability to achieve compatibility between user and environment